Rabies in Animal Bite Victims: How to Handle in North Kolaka Regency - Irma, Irma; Tina, Lymbran (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Rabies is one of the most important zoonoses in the world with a high impact on public health. Rabies disease in Indonesia is one of the public health problems with a high level of endemicity that has spread in 24 out of 34 provinces in Indonesia. In Indonesia, there are an average of 80,861 cases and 103 deaths per year from rabies transmitting animal bites (GHPR). From January to May 2019, there were 41 GHPR cases and 1 death case or 2.4% CFR in North Kolaka Regency. This research is descriptive with a qualitative approach. The population in this study is 42 cases of GHPR, all of which act as samples. The results showed that most cases of rabies were experienced by women (52.4%), the age of most people with rabies was the occupations of most of the sufferers (23.8%) were students and housewives, the ownership status of the animals was mostly wild animals (66.67%), and the bite history was mostly unprovoked (92.8%). This study recommends that joint efforts are needed to control rabies from the animal and human health sectors with a synergistic approach.